(untitled) (The Pakistan Development Review, 2010)
In recent years, the importance of historic events in the socioeconomic development of countries has emerged as an important area of research. There is a growing interest in determining the impact of historic events and conditions such as colonial rules, institutions, and factor endowments on the economic and social circumstances of countries today. Furthermore, the levels of development in the early decades of newly independent territories can have long term effects on the progress of those regions [Nunn (2007, 2009); Olsson and Hibbs (2005); Acemoglu, Johnson, and Robinson (2001); Engerman and Sokoloff (2000); La Porta, et al. (1998)].